The Role of Leadership and Digital Culture in Enhancing Organizational Sustainability in Higher Education: A Case Study at Universitas Kristen Indonesia Tomohon - Sammy Rommy Novie Korua; Peggy Adeline Mekel; Priskila Gissela Marlia Walangitan (SOSIOEDUKASI, 2025)
This study explores the interaction between leadership, digital culture, and organizational sustainability within the context of digital transformation at Universitas Kristen Indonesia Tomohon (UKIT), a faith-based higher-education institution in Eastern Indonesia. Employing a qualitative case study design, data were collected through in-depth interviews with 15 key informants, strategic document analysis, and observational notes. Thematic analysis revealed that value-driven transformative leadership serves as the central catalyst for digital adoption, with senior leaders actively modeling digital practices and framing technology as an extension of the Christian mission and service. The concept of "digitalization with heart" emerged as a powerful narrative that reduced resistance and fostered moral legitimacy among stakeholders. While digital culture remains in transition, generational differences and structural barriers are gradually being addressed through communities of practice and meaning-making processes that align innovation with the institutional identity. The integration of religious values into digital initiatives enabled a unique form of cultural alignment, distinguishing UKIT from secular transformation models. The impact on organizational sustainability is evident across the academic, operational, financial, and social dimensions, including improved graduation rates, reduced paper dependency, cost savings, and expanded outreach to marginalized communities. The findings suggest a reciprocal relationship among leadership, culture, and sustainability, forming a context-sensitive model of digital transformation grounded in ethical commitment and a shared vision. This study contributes to the literature by demonstrating how resource-constrained institutions can achieve sustainable digital change through holistic, value-based, and participatory approaches. It also offers practical insights for leaders of faith-based and regional universities navigating digital evolution.